An Improved Bilinear Interpolation Algorithm Using Center Coordinates of Pixels - Lu, Jing; Xia, Min; Li, Wei; Yang, Ke-Cheng (Sensors & transducers, 2013)
How to guarantee high image quality is the key point when converting standard-definition television (SDTV) images to high-defmition television (HDTV) images. Unfortunately, the change of pixel shape from rectangular to square makes traditional interpolation methods inappropriate because traditional methods are based on integer coordinates. In this paper, a novel interpolation algorithm using center coordinates of pixels (IAUCCP) is proposed. The color value of each pixel on HDTV images is revised by correcting the pixel's xy coordinates. Considering the huge enlarging multiples, sharpening treatment is done to the HDTV images after interpolating. Experiments show that our method greatly improves the HDTV image quality comparing with traditional interpolation algorithms. [PUBLICATION ABSTRACT]